Metal–organic framework-based nanomaterials for adsorption and photocatalytic degradation of gaseous pollutants: recent progress and challenges - Wen, Meicheng; Li, Guiying; Liu, Hongli; Chen, Jiangyao; An, Taicheng; Yamashita, Hiromi (Environmental science. Nano, 2019)
The development of porous nanomaterials with high efficiency for environmental remediation has been attracting significant attention and becoming an important topic recently. Metal–organic frameworks (MOF) are hybrid inorganic–organic porous materials containing a metal–oxygen cluster and organic molecules, which are becoming an alternative to traditional inorganic porous materials, such as zeolite and silica, for environmental remediation owing to their fascinating characteristics. Recent studies have demonstrated that MOF are one of the most efficient adsorbents or catalysts in gas separation, solar energy conversion and photocatalytic applications. This review mainly summarizes the recent progress on the adsorptive and degradation treatment of various gaseous pollutants by MOF materials. In this review, the physical and chemical adsorption of gaseous pollutants in air by MOFs will be discussed, and strategies for maximizing the adsorption capacity by tuning the physical and chemical properties of MOFs at the atomic level are systematically summarized. In particular, a promising strategy based on the synergistic effect of adsorption-concentrated photocatalytic oxidation of gaseous pollutants with this newly emerging MOF is also introduced, as it holds great potential in the treatment of gaseous pollutants in consideration of its high efficiency, low cost and being free from secondary pollution. In the end, the challenges faced, the prospects, and our personal perspective on future research directions are also estimated and elucidated.